Modern Pedagogical Approaches and Their Impact on the Quality of Education - Qobilova , Muslima; Charos , Dovutovna (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This article analyzes the theoretical foundations of modern pedagogical approaches, their positive impact on the quality of education, and the possibilities of their practical implementation. It highlights the important role of interactive and innovative methods in engaging students in the learning process, developing their independent thinking, and supporting their creative approaches.